Community Eagerness and Participation for Supporting Eliminate Malaria - SHAHANDEH, Khandan (Iran J Public Health, 2015)
BACKGROUND: This study was undertaken to identify key elements for obtaining community interest and motivate them to support eliminate malaria in the places that malaria is no longer a perceived threat. METHODS: Sequential explanatory mixed methods research design used to provide more comprehensive evidence research. A questionnaire was developed after reviewing the literature relating to community participation for malaria elimination and used to collect data from three native people, Iranian migrant and foreign immigrant groups. The variables included access to educational facilities, services, social support, social supporters, trust, and supportive norms were assessed. We also employed an ethnographic design involving: observation participant (PO), Key informant interviews (KIIs), and focus group discussions (FGDs). RESULTS: The results revealed that predisposing, enabling and reinforcing factors had association with community involvement. Less than 50% of total respondents reported have access to educational sessions, most of them were unaware of available and affordable services. Differences views regarding to social support influence have been found among respondents. Although patterns of social interactions were almost similar in all residents, frequencies of interactions were varied. Three thematic areas emerged including perceptions on involvement, potential barriers, and focus areas for the training community members. CONCLUSION: These findings indicate needs for greater understanding about how to strengthen community involvement with emphasize for community capacity building. This research has benefit to national and regional efforts to increase community involvement as a source for effective actions on malaria elimination.